EFFECT OF FOLIAR APPLICATION OF AMINOACIDS ON PLANT YIELD AND PHYSIOLOGICAL PARAMETERS IN FABA BEAN PLANTS IRRIGATED WITH SEAWATER (2015)
Salinity decreases yield in arid and semi-arid areas. With increasing demand for irrigation water, alternative sources are being sought. Seawater salinity was previously considered unusable for irrigation. However, this water can be used successfully to grow crops under certain conditions. Amino acids is well known biostimulant which has positive effects on plant growth and yield, and significantly mitigates the injuries caused by abiotic stresses Therefore, in the present study, the effect of exogenously treatment amino acid on faba bean plant growing under sea water salt stress was investigated. Reduction of salinity damage in faba bean by using a mixture of amino acids to improve morphological and biochemical parameters, and thus raising the level of plant yield was tested. A pot experiment was conducted to alleviate the harmful effects of seawater salinity on faba bean cv. Giza 843 by foliar spraying of an amino acid mixture with different concentrations (0.0, 500, 1000 or 1500 mg L-1). Irrigation of faba bean plants with seawater levels of 3.13 and 6.25 dS m-1 led to significant reductions in plant height, number of leaves plant, fresh and dry weight of shoots, photosynthetic pigments, total carbohydrates, polysaccharides, nucleic acid DNA and RNA contents of faba bean leaves. Seawater salinity induced higher contents of Na+ and Cl- and decreased contents of K+, K+:Na+, Ca2+, Mg2+ and P3+. Irrigation of faba bean plant with different levels of seawater decreased seed yield and total dry weight per plant compared with those irrigated with tap water. Also, total carbohydrates and total protein contents in seeds were reduced by increased seawater salinity levels. Amino acid application as foliar spray significantly improved all the reduced parameters due to seawater stress. However, the highest level of amino acid of 1500 mg L-1 exerted the strongest effect in alleviating the harmful effect of seawater salinity stress. Efecto de la aplicación foliar de aminoácidos sobre el rendimiento y parámetros fisiológicos en plantas de haba irrigadas con agua de marLa salinidad disminuye el rendimiento en zonas áridas y semiáridas. Con el aumento de la demanda de agua de riego, se están buscando fuentes alternativas. El agua de mar se consideró previamente inutilizable para irrigación debido a su salinidad. Sin embargo, esta agua puede ser utilizada con éxito en cultivos bajo ciertas condiciones. Los aminoácidos son bioestimulantes bien conocidos por sus efectos positivos sobre el crecimiento y rendimiento, y por mitigar significativamente las lesiones causadas por estrés abióticos. Por lo tanto, en el presente studio se investigó el efecto del tratamiento exógeno con aminoácidos sobre plantas de haba que crecen bajo estrés salino por irrigación con agua de mar. Se evaluó la reducción de daños por salinidad en plantas de haba mediante el uso de una mezcla de aminoácidos para mejorar los parámetros morfológicos y bioquímicos, y por lo tanto elevar el nivel de rendimiento de la planta. Se desarrolló un experimento en macetas para paliar los efectos nocivos de la salinidad del agua de mar en el cv. De haba Giza 843 por aspersion foliar de una mezcla de aminoácidos con diferentes concentraciones (0, 500, 1000 o 1500 mg L-1). El riego de plantas de haba con niveles de agua de mar de 3.13 y 6.25 dS m-1 condujo a reducciones significativas en la altura de planta, número de hojas de la planta, peso fresco y seco de los brotes, y en el contenido foliar de pigmentos fotosintéticos, carbohidratos totales, polisacáridos y ácidos nucleicos (ADN y ARN). La salinidad del agua de mar indujo un mayor contenido de Na+ y Cl- , y una disminución del contenido de K+, K+: Na+, Ca2+, Mg2+ y P3+. El riego de plantas de haba con diferentes niveles de agua de mar redujo el rendimiento de semillas y el peso seco total por planta en comparación con las regadas con agua corriente. Además, el contenido de carbohidratos y proteína total en las semillas disminuyeron con el aumento de los niveles de salinidad del agua de mar. La aplicación de aminoácidos por aspersion foliar increment significativamente todos los parámetros reducidos debido al estrés por agua de mar. Sin embargo, el más alto nivel de aminoácidos (1500 mg L-1) ejerce el máximo efecto en el alivio de los efectos nocivos de estrés por salinidad del agua de mar.